2023
DOI: 10.3389/fmicb.2023.1209358
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium pyruvate in maintaining the survival and cytotoxicity of Staphylococcus aureus under high glucose conditions

Abstract: Glucose is a crucial carbon source for the growth of Staphylococcus aureus, but an excess of glucose is detrimental and even leads to cell death. Pyruvate, the central metabolite of glycolysis, has been shown to have anti-inflammatory and antioxidant properties. This study aimed to investigate the protective effect of pyruvate on S. aureus under high glucose conditions. Sodium pyruvate greatly increased the cytotoxicity of S. aureus strain BAA-1717 to human erythrocytes and neutrophils in vitro. However, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…High levels of sugar breed pathogen development, leading to DFIs (Seo et al, 2021). However, excessive glucose intake hinders the production of virulence factors and reduces the severity of S. aureus infections (Seidl et al, 2008;Dufresne et al, 2022;Chen et al, 2023). Herein, it was found that S. aureus strains isolated from DFUs exhibited higher cytotoxicity to human erythrocytes.…”
Section: Introductionmentioning
confidence: 98%
“…High levels of sugar breed pathogen development, leading to DFIs (Seo et al, 2021). However, excessive glucose intake hinders the production of virulence factors and reduces the severity of S. aureus infections (Seidl et al, 2008;Dufresne et al, 2022;Chen et al, 2023). Herein, it was found that S. aureus strains isolated from DFUs exhibited higher cytotoxicity to human erythrocytes.…”
Section: Introductionmentioning
confidence: 98%